If a . b + b . c + c . a = 0 and ∣ a + b + c ∣ 2 = k , find the value of l such that
∣ a + b − c ∣ 2 + ∣ a − b + c ∣ 2 + ∣ − a + b + c ∣ 2 = l ⋅ k .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Just expanding the terms in the L.H.S of the question results in 27 terms. Not quite an efficient method. Also, just substituting suitable values like i, j and k is not that satisfying of a solution
Problem Loading...
Note Loading...
Set Loading...
C o n s i d e r [ ( a + b + c ) + ( a + b − c ) ] ⋅ [ ( a + b + c ) − ( a + b − c ) ] . I t r e d u c e s t o 2 ( a + b ) ⋅ ( 2 c ) = 4 ( a ⋅ c + b ⋅ c ) ⟶ e q n 1 H o w e v e r , u s i n g t h e f o r m u l a ( c + d ) ⋅ ( c − d ) = ∣ c ∣ 2 − ∣ ∣ ∣ d ∣ ∣ ∣ 2 , w e g e t ∣ ∣ ∣ a + b + c ∣ ∣ ∣ 2 − ∣ ∣ ∣ a + b − c ∣ ∣ ∣ 2 ⟶ e q n 2 E q u a t i n g 1 a n d 2 , w e g e t 4 ( a ⋅ c + b ⋅ c ) = ∣ ∣ ∣ a + b + c ∣ ∣ ∣ 2 − ∣ ∣ ∣ a + b − c ∣ ∣ ∣ 2 ⟶ e q n 3 S i m i l a r l y , 4 ( a ⋅ b + c ⋅ b ) = ∣ ∣ ∣ a + b + c ∣ ∣ ∣ 2 − ∣ ∣ ∣ a − b + c ∣ ∣ ∣ 2 ⟶ e q n 4 A n d , 4 ( b ⋅ a + c ⋅ a ) = ∣ ∣ ∣ a + b + c ∣ ∣ ∣ 2 − ∣ ∣ ∣ − a + b + c ∣ ∣ ∣ 2 ⟶ e q n 5 A d d i n g e q u a t i o n s 3 , 4 , a n d 5 : 8 ( a ⋅ b + b ⋅ c + c ⋅ a ) = 3 ∣ ∣ ∣ a + b + c ∣ ∣ ∣ 2 − ( ∣ ∣ ∣ a + b − c ∣ ∣ ∣ 2 + ∣ ∣ ∣ a − b + c ∣ ∣ ∣ 2 + ∣ ∣ ∣ − a + b + c ∣ ∣ ∣ 2 ) A s a ⋅ b + b ⋅ c + c ⋅ a = 0 , w e g e t ∣ ∣ ∣ a + b − c ∣ ∣ ∣ 2 + ∣ ∣ ∣ a − b + c ∣ ∣ ∣ 2 + ∣ ∣ ∣ − a + b + c ∣ ∣ ∣ 2 = 3 ∣ ∣ ∣ a + b + c ∣ ∣ ∣ 2 . ∴ l = 3 .